Are open‐Label Placebos Ethical? Informed Consent and Ethical Equivocations. (3rd February 2016) - Blease, Charlotte; Colloca, Luana; Kaptchuk, Ted J.
Abstract: The doctor‐patient relationship is built on an implicit covenant of trust, yet it was not until the post‐World War Two era that respect for patient autonomy emerged as an article of mainstream medical ethics. Unlike their medical forebears, physicians today are expected to furnish patients with adequate information about diagnoses, prognoses and treatments. Against these dicta there has been ongoing debate over whether placebos pose a threat to patient autonomy. A key premise underlying medical ethics discussion is the notion that the placebo effect necessitates patient deception. Indeed, the American Medical Association guidelines imply that placebo treatment necessary entails a form of deception. As a consequence of this assumption, the fulcrum of debate on the use of placebo treatment has hinged on whether that deception is ever justified. Recently performed experiments with open‐label transparently prescribed placebos have begun to challenge the notion that deception is necessary in eliciting the placebo effect and such effects necessarily involve a binary distinction between autonomy and beneficence. In this article we focus on the content of disclosures in distinctive open‐label, transparently disclosed placebo studies and inquire whether they might be said to invoke deception in clinical contexts, and if so, whether the deception is unethical. We find that open placebos may be said to involve equivocation over how placebos work. However, drawing on surveys of patient attitudes we suggest that this equivocation appears to be acceptable to patients. We conclude that open placebos fulfil current American Medical Association guidelines for placebo use, and propose future research directions for harnessing the placebo effect ethically.